Case Study: Factors Causing Low Student Activeness in Grade 5 at SDN 05 Muara Ilai in the IPAS Subject - Fransiskus Ricardo; Vikram Yuda Octa Firandhi; Metroyadi Metroyadi (MASI Mandiri Edukasi, 2026)
This study investigates the factors contributing to low student activeness in Grade 5 at SDN 05 Muara Ilai in the Integrated Natural and Social Sciences (IPAS) subject. The research aims to identify and analyze the internal and external factors that influence students’ participation during classroom learning. A qualitative approach with a case study design was employed to gain an in-depth understanding of the phenomenon. Data were collected through classroom observations, interviews, and documentation involving the class teacher, the student’s seatmate, and the previous class teacher. The findings reveal that low student activeness is caused by the interaction of multiple factors. Internal factors include biological conditions, particularly health-related issues, which significantly affect students’ physical readiness, concentration, and energy levels. These biological factors are closely linked to psychological aspects such as low motivation, lack of self-confidence, emotional withdrawal, and cognitive difficulties in maintaining focus and processing information. External factors also contribute to the problem, including limited parental support, unfavorable home learning environments, inadequate school facilities, limited health services, and teacher-centered instructional methods dominated by lectures. Socio-cultural influences, such as peer interaction patterns and limited social support regarding health awareness, further affect student participation. In conclusion, low student activeness in IPAS learning arises from the complex interaction of internal and external conditions. Improving student engagement requires integrated efforts addressing health, learning environments, and social support systems.